PENGARUH KOMUNIKASI INTERPERSONAL, TEAMWORK TERHADAP KINERJA KARYAWAN DI PT LUHAI INDUSTRIAL (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
ABSTRACT Employee performance is significantly affected by interpersonal communication, teamwork related to the organization. The causal study reported here aims to test the hypothesis. It was conducted through a survey at PT Luhai Industrial, on a sample of 53 employees using the boring sampling method. data for each variable was collected separately by the respondents who filled out the questionnaire. path technique is applied to analyze the data previously treated with procedural and correlation. the results prove that employee performance is directly influenced by interpersonal communication and team work. The findings show that variations in employee performance are influenced by interpersonal communication and teamwork within the organization. This further implies the need to consider the variables of performance, interpersonal communication, and teamwork in the planning of human resource development strategies at PT Luhai Industries under study.